2004
DOI: 10.1007/s00216-004-2558-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of total effective xenoestrogen burden in adipose tissue and identification of chemicals responsible for the combined estrogenic effect

Abstract: Test systems to screen for estrogenicity and appropriate biomarkers of human exposure are required for epidemiological studies of endocrine disruption. We addressed these issues by developing and standardising a method to assess the total estrogenic xenobiotic burden in human adipose tissue. In this study, which is the continuation of a previous work, we have improved the protocol for extensive fractionation of a higher number of tissue samples in order to investigate bioaccumulated xenoestrogens that are cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 40 publications
2
60
2
Order By: Relevance
“…Pesticides were selected using a combination of exposure scores and data about receptor-mediated antiandrogenic activity [see Supplemental Material, Figure 1 (Fernández et al 2004). Each pesticide was assigned four scores, with each ranging from 1 to 10: a) maximum food residue level (European Commission 2008); b) estimated daily dietary intake (FAO/WHO 2011); c) frequency of detection in fruits and vegetables (EFSA 2009), with a score of 5 assigned when data were not available; and d) a score according to the number of times pesticides were listed as one of the top 10 pesticides identified in fruits and cereals in Europe (a frequency score), with a score of 0 assigned if they were never listed (European Commission 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Pesticides were selected using a combination of exposure scores and data about receptor-mediated antiandrogenic activity [see Supplemental Material, Figure 1 (Fernández et al 2004). Each pesticide was assigned four scores, with each ranging from 1 to 10: a) maximum food residue level (European Commission 2008); b) estimated daily dietary intake (FAO/WHO 2011); c) frequency of detection in fruits and vegetables (EFSA 2009), with a score of 5 assigned when data were not available; and d) a score according to the number of times pesticides were listed as one of the top 10 pesticides identified in fruits and cereals in Europe (a frequency score), with a score of 0 assigned if they were never listed (European Commission 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Placentas were collected at delivery from the cohort, and 17 OC pesticides (dichlorodiphenyltrichloroethane (DDT) isomers and metabolites, endosulphan isomers and metabolites, aldrin, endrin, dieldrin, lindane, hexachlorobenzene, methoxychlor and mirex) were extracted from tissue samples by a previously described method, which was developed to separate natural oestrogens (a fraction) from more lipophilic xeno-oestrogens (b fraction) without destroying either (34,35).…”
Section: Quantification Of Oc Pesticides and Oestrogenicity In The Plmentioning
confidence: 99%
“…The total effective xeno-oestrogenic burden (TEXB) of the a fraction (a-TEXB) and the b fraction (b-TEXB) was estimated in the placenta samples by using the E-Screen bioassay (34,35). The a-TEXB can be considered a marker of the TEXB of environmental organohalogenated oestrogens (35).…”
Section: Quantification Of Oc Pesticides and Oestrogenicity In The Plmentioning
confidence: 99%
“…They can cause chronic toxicity nonHodgkin's lymphoma in adults and children after their long-term exposure [8]. Some other studies also showed that these compounds had endocrine-disrupting activity [9]. Polychlorinated biphenyls (PCBs) are also hazardous substances due to their toxic properties.…”
Section: Introductionmentioning
confidence: 98%